Chromosomal mapping of a major quantitative trait locus regulating compensatory renal growth in the rat - Pravenec, Michal; Zidek, Vaclav; Musilova, Alena; Křen, Vladimir; Bila, Vlasta; Nicolantonio, Robert DI (Journal of the American Society of Nephrology, 2000)
Despite extensive research conducted over the past century, the mechanisms of compensatory renal growth (CRG) remain a mystery. Insight into the mechanisms that regulate CRG might be gained by identifying genetic factors that influence this complex phenotype. In a large set of recombinant inbred strains derived from the spontaneously hypertensive rat and the Brown Norway rat, a genome scan for quantitative trait loci (QTL) that regulate CRG was performed. The CRG score was expressed as a ratio of the weight of the remnant right kidney at 8 wk of age to the weight of the left kidney at 5 wk of age, both adjusted for body weight. QTL mapping was performed using Map Manager QT and the strain distribution patterns of more than 600 genetic markers. It was found that CRG after unilateral nephrectomy is a multifactorially determined trait with a substantial genetic component. The heritability of CRG approached 40%. Genome wide scan analysis revealed significant evidence of linkage to a region of rat chromosome 4 designated Crg 1 that accounted for more than 50% of the additive genetic variance of CRG in the recombinant inbred strains. The detection of a major QTL influencing CRG in the rat should provide new opportunities for identifying mechanisms that regulate this historically enigmatic phenomenon and may also have implications for research on the pathogenesis of end-stage kidney disease.
Keywords: rekombinace genetická; velikost orgánu; Humans; Recombination, Genetic; lidské chromozomy, pár 4; Adaptation, Physiological; potkani inbrední BN; genetické markery; ledviny; Quantitative Trait, Heritable; Kidney; krysa rodu Rattus; lidé; zvířata; Rats, Inbred BN; Genetic Linkage; potkani inbrední SHR; Chromosome Mapping; genetická vazba; Genetic Markers; fyziologická adaptace; Rats; mapování chromozomů; Animals; Chromosomes, Human, Pair 4; Organ Size; Nephrectomy; nefrektomie; Rats, Inbred SHR; kvantitativní znak dědičný